Exploring the Causes of Squatting in the Balkhu Corridor of Kathmandu - Acharya, Bala Ram (Dhaulagiri Journal of Sociology and Anthropology, 2024)
Squatting persists primarily in urban areas due to fulfil housing needs and lack of viable livelihood options for marginalized people. In Nepal, it is generally seen as a combination of economic and political factors. The study aims to assess the poverty levels among the squatters in the Balkhu Corridor of Kathmandu and to investigate the causes of squatting as a manifestation of urban poverty. The research utilizes a qualitative approach. The results indicate that squatters in the Balkhu Corridor lack options, resources, support, and government aid meant for the homeless. The research shows that landlessness is not the main reason for squatting among migrant families in urban areas. Instead, the financial strain of meeting housing, education, healthcare, and other essential needs exacerbates the difficulties faced by these families, ultimately pushing them towards squatting. Nepal's ruling and opposition parties utilize squatter communities for political gain. The flow of squatting in urban regions of Nepal can be linked to notable historical occurrences such as the People's Movement in the 1990s and the internal armed conflict spanning from 1996 to 2006.